EFFORTS TO IMPROVE STUDENT PKN LEARNING OUTCOMES THROUGH THE APPLICATION OF THE COOPERATIVE LEARNING MODEL THREE STAY ONE STRAY (TSOS) TYPE - Nasmi Nasmi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research is based on the fact that the involvement of students who are lacking in learning and the low learning outcomes of PKN students. This study aims to improve student learning outcomes through the application of the three stay one stray cooperative learning model (TSOS) which facilitates students to actively learn to find the information they need in learning. The research was conducted at SDN 002 Muara Lembu with 21 students as research subjects. This research is a class action research conducted in class III B. The research instrument used was an observation sheet and a test of learning outcomes. The results showed that an increase in learning activities after the three stay one stray cooperative learning model was applied where in the first cycle the teacher's action was 57% with a sufficient category to be 77% which was included in the good category, the percentage of student activities in the first cycle was equal to 62% to 80% in the second cycle which is a good category, and student learning outcomes have increased from cycle I which has an average of 72 (enough) to 80 which is included in both categories. The conclusion based on the results of the study is that through the application of the three stay one stray type of cooperative learning model (TSOS) can improve student learning outcomes in class III B SDN 002 Muara Lembu.